ANALISIS INDUSTRI CAHAYA BUMI SLAMET MARTAPURA DAN STRATEGI DIFERENSIASI TERHADAP KEUNGGULAN BERSAING(Studi Pada Toko Permata Sentral Delima) - admin admin; Akhmad Supriyanto; Doni Setiadi; Aditya Ferdiawan (Universitas Lambung Mangkurat, 2020)
This study aims to determine and analyze whether product differentiation strategies, service differentiation, image differentiation have a simultaneous and partial effect on competitive advantage and identify the key success factor (KSF) of Cahaya Bumi Slamet Martapura Shops its influence on competitive advantage at Permata Central Delima Martapura Stores. This type of research is causality research with a sampling technique that is accidental sampling. Primary data was collected using a questionnaire instrument while secondary data was obtained by collecting various data about the company and the level of competition. Secondary data and primary data were analyzed descriptively by using Porter's Five Forces of Competition analysis and using multiple linear regression analysis. The results of the study prove that the product differentiation strategy, service differentiation and image differentiation simultaneously have a significant effect on competitive advantage. Partially, product differentiation strategy and service differentiation have no significant effect. While the image differentiation strategy has a significant effect on competitive advantage. Service differentiation strategy does not have a dominant effect on competitive advantage. The results of the industry and competition analysis identify the Key success factors (KSF) that create a competitive advantage at the Cahaya Bumi Selamat (CBS) Martapura shops consisting of; economies of scale, capital, services and control of access to raw materials.